Bibliometric Analysis, Evolution and Trends of Happiness Management in Scientific Literature. - Rando-Cueto, Dolores; Núñez-Sánchez, José Manuel; Fernández-Díaz, Elena; De-las-Heras-Pedrosa, Carlos (Universidad de Sevilla, 2023)
This study aims to analyse the concept of “Happiness management” in the scientific literature due to the growing interest in aspects related to happiness management in social and professional spheres, which has resulted in recent research. A systematic review of publications is carried out in order to examine the current situation in terms of scientific production and to analyse the evolution and trends in the study. In addition, using the Scopus database and the VOS viewer software, records were obtained from which a bibliometric analysis was carried out. Among the results achieved, the positioning of Spain as a benchmark country in the international literature on “Happiness management” and the influence of COVID-19 on the spread and citation of publications stands out. The scientific contributions on this subject and its influence on future research is a growing field of study and of interest for the improvement of quality of life and organizational well-being
Keywords: Satisfacción en el trabajo; Sociología de las organizaciones; Happiness management; Spain; VOS viewer; COVID-19; Bibliometric analysis; Organizational well-being